Chance-constrained energy-reserve co-optimization scheduling of wind-photovoltaic-hydrogen integrated energy systems. (1st March 2023) - Wu, Gang; Li, Ting; Xu, Weiting; Xiang, Yue; Su, Yunche; Liu, Jiawei; Liu, Fang
Abstract: An optimal energy-reserve scheduling model of wind-photovoltaic-hydrogen integrated energy systems (WPH-IES) with multi-type energy storage devices including electric, thermal and hydrogen is presented in this paper. The chance-constrained programming (CCP) theory is utilized to model the impact of renewable and load uncertainties on reserve constraints. Considering the non-convex of proposed CCP model, an improved discretized step transformation (DST) method is proposed to transform the CCP problem into a solvable mixed integer linear programming (MILP) formulation. In addition, a critical threshold value selection approach is developed to reduce the number of constraints and improve solution efficiency. Case studies demonstrate that the proposed energy-reserve model can reduce the total operating cost on the premise of ensuring the safety of system operation. The combined improved DST and critical threshold value selection method can reduce computational burden and improve the accuracy of scheduling results. Highlights: An optimal energy-reserve scheduling model of WPH-IES is proposed. The multi-type energy storage devices are considered. An improved discretized step transformation method is proposed.